Management of Patients Coinfected With HCV and HIV: A Close Look at the Role for Direct-Acting Antivirals - Naggie, Susanna (2012)
With the development of effective therapies against human immunodeficiency virus (HIV), hepatitis C virus (HCV) infection has become a major cause of morbidity and mortality among patients with both infections (coinfection). In addition to the high prevalence of chronic HCV, particularly among HIV-infected injection drug users, the rate of incident HIV infections is increasing among HIV-infected men who have sex with men, leading to recommendations for education and screening for HCV in this population. Liver disease is the second leading and, in some cases, a preventable cause of death among coinfected patients. Those at risk for liver disease progression are usually treated with a combination of interferon (IFN) and ribavirin (RBV), which is not highly effective; it has low rates of sustained virologic response (SVR), especially for coinfected patients with HCV genotype 1 and those of African descent. Direct-acting antivirals might overcome factors such as immunodeficiency that can reduce the efficacy of IFN. However, for now it remains challenging to treat coinfected patients due to interactions among drugs, additive drug toxicities, and the continued need for combination therapies that include pegylated IFN. Recently developed HCV protease inhibitors such as telaprevir and boceprevir, given in combination with pegylated IFN and RBV, could increase the rate of SVR with manageable toxicity and drug interactions. We review the latest developments and obstacles to treating coinfected patients.